1999
DOI: 10.1007/bf03026309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applied potential and solution temperature on the pitting corrosion of pure aluminium in sulphate ion-containing chloride solution

Abstract: Effects of applied potential and solution temperature T. on the pitting corrosion of pure aluminium (AI) were investigated in 0.01 M NaCI solutions containing various sulphate (SO, 2-) ion concentrations using a potentiodynamic polarisation experiment, the potentiostatic current transient technique, ac impedance spectroscopy and atomic force microscopy (AFM). The potentiodynamic polarisation curves showed a rise in the pitting potential E,, values and a simultaneous increase in anodic current density at potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…A suitable sulfate concentration in the etchant can lead to a deep and homogenously etched layer with high surface area [Ono & Habazaki 2009]. It was shown previously that sulfate ions could shift the pitting potential in the positive direction [Tomcsanyi et al 1989, Kim et al 1999, Lee et al 2000, Ono & Habazaki 2009. This was later interpreted as the elimination of the competitive adsorption of sulfate ions by chloride ions [Ono & Habazaki 2009].…”
Section: Influence Of the Electrolyte On The Electrograining Processmentioning
confidence: 97%
See 1 more Smart Citation
“…A suitable sulfate concentration in the etchant can lead to a deep and homogenously etched layer with high surface area [Ono & Habazaki 2009]. It was shown previously that sulfate ions could shift the pitting potential in the positive direction [Tomcsanyi et al 1989, Kim et al 1999, Lee et al 2000, Ono & Habazaki 2009. This was later interpreted as the elimination of the competitive adsorption of sulfate ions by chloride ions [Ono & Habazaki 2009].…”
Section: Influence Of the Electrolyte On The Electrograining Processmentioning
confidence: 97%
“…This was later interpreted as the elimination of the competitive adsorption of sulfate ions by chloride ions [Ono & Habazaki 2009]. The rise of the pitting potential indicates the impediment of pit initiation of pure aluminium by sulfate ions [Kim et al, 1999, Ono & Habazaki 2009. It was also observed that an excess of H 2 SO 4 in the electrolyte promotes the formation of an etched layer with uniform thickness, since the pit formation is suppressed on the aluminium surface [Ono & Habazaki 2009].…”
Section: Influence Of the Electrolyte On The Electrograining Processmentioning
confidence: 99%